Digital era of banking with special reference to cyber crime a critical study - Malik, Payal (Innovative Research Thoughts, 2017)
Customers are now able to access banking services via a variety of digital channels, including mobile devices, personal computers, and automated teller machines (ATMs). This is a direct result of the advent of the digital age. On the other hand, this transition has also resulted in a rise in cybercrime, as hackers and other cybercriminals have begun targeting financial institutions and their clients in order to steal, commit fraud, and engage in other illegal acts. the digital age of banking presents an overview of the digital banking environment, covering the many sorts of digital services supplied by banks and the benefits they bring to clients. a specific reference is made to cybercrime. phishing, spyware, identity theft, and ransomware are just some of the many forms of cybercrime that are rampant in the banking business.